2019
DOI: 10.1016/j.semcdb.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Genes and pathways in optic fissure closure

Abstract: Embryonic development of the vertebrate eye begins with the formation of an optic vesicle which folds inwards to form a double-layered optic cup with a fissure on the ventral surface, known as the optic fissure. Closure of the optic fissure is essential for subsequent growth and development of the eye. A defect in this process can leave a gap in the iris, retina or optic nerve, known as a coloboma, which can lead to severe visual impairment. This review brings together current information about genes and pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 183 publications
1
82
0
1
Order By: Relevance
“…Reduced rates of differentiation were most probably due to an increased number of proliferative EdU + /Ki67 + cells resulting in tissue expansion and bending (arrowhead in Fig J’ and ). Even if these morphological deformations might resemble a coloboma (), which normally results from a failure in ventral fissure closure (Patel & Sowden, ), transverse sections of the optic vesicle depict proper fusion of the ventral fissures in E13.5 Nr2f1 mutants (). Therefore, abnormal optic vesicle morphology observed in Nr2f1 mutants arises most probably from tissue bending due to excessive proliferation and delayed cell differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced rates of differentiation were most probably due to an increased number of proliferative EdU + /Ki67 + cells resulting in tissue expansion and bending (arrowhead in Fig J’ and ). Even if these morphological deformations might resemble a coloboma (), which normally results from a failure in ventral fissure closure (Patel & Sowden, ), transverse sections of the optic vesicle depict proper fusion of the ventral fissures in E13.5 Nr2f1 mutants (). Therefore, abnormal optic vesicle morphology observed in Nr2f1 mutants arises most probably from tissue bending due to excessive proliferation and delayed cell differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence of the invagination and morphogenesis of the early eye field into a bilayered optic cup, a transient opening known as the choroid fissure forms in the ventral optic cup which enables the hyaloid vasculature to enter the eye, and the optic nerve to exit . The choroid fissure must close such that retina and RPE tissue are properly contained within the eye, and failure of this process results in colobomas (reviewed in Gregory‐Evans et al, 2004; Williamson and FitzPatrick, 2014; Patel and Sowden, 2017) …”
Section: Introductionmentioning
confidence: 99%
“…16 The choroid fissure must close such that retina and RPE tissue are properly contained within the eye, and failure of this process results in colobomas (reviewed in Gregory-Evans et al, 2004; Williamson and FitzPatrick, 2014; Patel and Sowden, 2017). [22][23][24] As mentioned above, previous studies have identified or generated mab21l2 mutant zebrafish 4,6 which display ocular phenotypes. However, these ocular defects have not been fully documented and characterized, which is necessary for these zebrafish models to be useful in providing mechanistic insight into ocular defects in human patients with MAB21L2 mutations, as well as to begin to unravel the functions of the mab21l2 protein during ocular development.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of multiple patterns of Mendelian inheritance, incomplete penetrance, variable expressivity, genetic heterogeneity, and environmental factors make the genetic investigation of this disease particularly challenging (Chang et al, ; Skalicky et al, ; Williamson & FitzPatrick, ). Although several genes identified in animal studies are critical for optic fissure closure during eye development, very few are known to cause coloboma in humans (Brown et al, ; Patel & Sowden, ). On the other hand, reports of human mutations are often not complemented by experimental mechanistic evidence either in animal models or in cell culture (Bourchany et al, ; Chassaing et al, ; Graham et al, ; Kahrizi et al, ; Martinez‐Garay et al, ; Ng et al, ; Patel & Sowden, ; Wenger et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although several genes identified in animal studies are critical for optic fissure closure during eye development, very few are known to cause coloboma in humans (Brown et al, ; Patel & Sowden, ). On the other hand, reports of human mutations are often not complemented by experimental mechanistic evidence either in animal models or in cell culture (Bourchany et al, ; Chassaing et al, ; Graham et al, ; Kahrizi et al, ; Martinez‐Garay et al, ; Ng et al, ; Patel & Sowden, ; Wenger et al, ). In many cases, studies on coloboma genetics have focused on a select number of genes, and many have included syndromic conditions with severe ocular phenotypes (e.g., severe microphthalmia and anophthalmia; Gonzalez‐Rodriguez et al, ; Guo, Dai, Huang, Liao, & Bai, ; Mihelec et al, ; Morrison et al, ; Schimmenti et al, ; Williamson & FitzPatrick, ; X. Zhang et al, ; J. Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%